2008
DOI: 10.1182/blood-2008-02-140673
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors: lessons to learn from normal and malignant human B cells

Abstract: IntroductionThe human immune system is continuously challenged by commensal microflora as well as invasive infectious agents. The decision to mount a rapid and protective immune response to a pathogen is a consequence of the activation of the innate immune system via pattern recognition receptors, such as Toll-like receptors (TLRs), that sense microbial products. 1 TLR polymorphisms have been implicated in increased severity and predisposition to infection and septic shock 2 in both mice and humans. TLRs recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 79 publications
(121 reference statements)
3
105
1
6
Order By: Relevance
“…Data from multiple studies have identified a role for dysregulated B-cell TLR expression/ signaling in the etiology of lymphomas [30,31]. Our finding that B cells from cases exhibit significantly high levels of TLR2 expression support these reports.…”
Section: Discussionsupporting
confidence: 82%
“…Data from multiple studies have identified a role for dysregulated B-cell TLR expression/ signaling in the etiology of lymphomas [30,31]. Our finding that B cells from cases exhibit significantly high levels of TLR2 expression support these reports.…”
Section: Discussionsupporting
confidence: 82%
“…Recent studies have suggested a role of microenvironment stimuli in sustaining MCL (1). TLRs mediate cell responses to specific pathogen-associated molecular patterns (34). In that sense, we found mutations of TLR2 in two SOX11-negative/ IGHV-mutated MCL, and these mutations were associated with increased production of IL-1RA and IL-6 by the tumor cells.…”
Section: Discussionmentioning
confidence: 55%
“…38 Intriguing aspect of TLR stimulation in B-CLL is their ability to induce apoptosis and cell death in leukemic cells which could be of great relevance for their use in the clinics. TLR-7 and TLR-9 agonists were reported to induce apoptosis in B-CLL cells.…”
Section: Cancer Cell Biologymentioning
confidence: 99%